Updated efficacy and safety data from a phase II, single-arm, open-label study of durvalumab plus gemcitabine, cisplatin, and nab-paclitaxel (DurGAP) in resectable biliary tract cancer - Huikai Li; Yang Liu; Xihao Zhang (The Lancet Regional Health. Western Pacific)
Background: Our previous research (2024 ASCO Abstract: e16260) highlighted the efficacy and safety data of DurGAP in resectable biliary tract cancer (BTC). This study aims to provide an updated analysis of the safety and efficacy of neoadjuvant DurGAP for resectable BTC in our latest cohort of 30 patients. The current results demonstrate consistent outcomes. Detailed data are presented herein. Methods: Resectable, treatment-naïve BTC pts were enrolled and administered 3 cycles of neoadjuvant durvalumab (1000 mg, iv, d1, q3w) + GAP (gemcitabine 1000 mg/m2, cisplatin 25 mg/m2, Nab-paclitaxel 100 mg/m2, d1, d8, 21d cycle). Primary endpoints included assessing Adverse Events (AEs), Objective Response Rate (ORR) and Disease Control Rate (DCR). Secondary endpoints comprised R0 resection rate, Recurrence-Free Survival (RFS), Overall Survival (OS). Findings: Between Feb, 2023 to Aug, 2024, a total of 30 patients were enrolled, 13 (43.3%) were male, all with ECOG 0 and 24 (80.0%) presenting with N1 status. Median age: 65.3 years. Primary sites: intrahepatic (40.0%), extrahepatic (26.7%), gallbladder (33.3%). Median follow-up: 9.45 months; all pts received ≥2 neoadjuvant cycles. The ORR was 60%, with 18 pts demonstrating partial responses (PR). The DCR was 86.7% with 18 PR and 8 stable disease (SD) responses. The most common treatment-related adverse events (TRAEs) were increased ALT/AST (26.7%), anemia (23.3%), hypoalbuminemia (16.7%). Grade ≥3 TRAEs occurred in 2 (6.7%) pts. 16 pts underwent resection, comprising 12 PR, 2 SD, and 2 pts deemed eligible for surgery post-assessment despite a PD response, achieving R0 resection in 15 (93.8%) of cases. 14 pts did not undergo resection, with reasons including patient refusal (4 PR, 1 SD), not meeting resection criteria (2 PD), lost to follow-up (1 PR, 1 SD), and still under active follow-up (1 PR, 4 SD). Interpretation: Neoadjuvant DurGAP demonstrated a consistent and promising ORR and DCR, with a tolerable safety profile, warranting further investigations in a larger cohort. Clinical trial information: NCT05640791. Research Sponsor: None.